ANALISIS TOKOH UTAMA PADA NOVEL NEGERI PARA BEDEBAH DAN NEGERI DI UJUNG TANDUK - Sugiatno, Septian Utut (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2018)
Abstract:The focus of this research is to describe the personality of the main characters in the novels Negeri Para Bedebah and Negeri di Ujung Tanduk by Tara Liye based on Sigmund Freud personality theory of psychoanalysis experienced by the main characters and the attitude of the main characters in dealing with the conflict. The data collection technique was documentary study. The tool for data collection in this study was the researcher himself as a key instrument. The attitude of the main characters in these novels is based on Sigmund Freud personality theory of psychoanalysis that leads to Ego which reveals more personality considering the reality in this conflict. The reality consideration that eventually leads to different encouraging attitude, influences, or supports the basic personality (id) and not encouraging, influencing, or supporting the basic personality (id). While the super ego in these novels is not much because the main characters have more consideration of the reality compared to paying attention toward spiritual values or norms. Therefore the main characters in these novels address the conflict with encouragement, support, or affect the basic personality (id).Â Keywords: main characters, novel, literary psychologyÂ